2019
DOI: 10.1186/s13568-019-0866-6
|View full text |Cite
|
Sign up to set email alerts
|

A genetic tool for production of GFP-expressing Rhodopseudomonas palustris for visualization of bacterial colonization

Abstract: Development of a genetic tool for visualization of photosynthetic bacteria (PSB) is essential for understanding microbial function during their interaction with plant and microflora. In this study, Rhodopseudomonas palustris GJ-22-gfp harboring the vector pBBR1-pckAPT-gfp was constructed using an electroporation transformation method and was used for dynamic tracing of bacteria in plants. The results showed that strain GJ-22-gfp was stable and did not affect the biocontrol function, and the Confocal Laser Scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The background fluorescence produced by photosynthetic microbes like R. palustris can complicate the use of such an important tool. The gene for green fluorescent protein (GFP) has been expressed in R. palustris CGA009 ( Doud et al, 2017 ) as well as another R. palustris strain, GJ-22 ( Zhai et al, 2019 ), but the use of other fluorescent proteins has not been reported. To determine the fluorescent reporter best suited for work in R. palustris , the fluorescence of wild type R. palustris was determined (Materials and Methods) for the excitation and emission wavelengths of GFPuv, enhanced yellow fluorescent protein (eYFP), and monomeric red fluorescent protein (mRFP) ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…The background fluorescence produced by photosynthetic microbes like R. palustris can complicate the use of such an important tool. The gene for green fluorescent protein (GFP) has been expressed in R. palustris CGA009 ( Doud et al, 2017 ) as well as another R. palustris strain, GJ-22 ( Zhai et al, 2019 ), but the use of other fluorescent proteins has not been reported. To determine the fluorescent reporter best suited for work in R. palustris , the fluorescence of wild type R. palustris was determined (Materials and Methods) for the excitation and emission wavelengths of GFPuv, enhanced yellow fluorescent protein (eYFP), and monomeric red fluorescent protein (mRFP) ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…Growth curves of gfp-labelled and wildtype M. salsuginis TNMB03 were measured to determine whether the addition of gfp affects growth and metabolism. Wild-type strain M. salsuginis TNMB03 and TNMB03-gfp were cultured in the same conditions and population count was taken at different time intervals (Zhai et al 2019). The observed growth pattern did not show any differences between gfp transformed and wild type M. salsuginis (data not shown).…”
Section: Green Fluorescent Protein Labelling Of M Salsuginis Tnmb03mentioning
confidence: 96%
“…The background fluorescence produced by photosynthetic microbes like R. palustris can complicate the use of such an important tool. The gene for green fluorescent protein (GFP) has been expressed in R. palustris CGA009 (Doud et al, 2017) as well as another R. palustris strain, GJ-22 (Zhai et al, 2019), but the use of other fluorescent proteins has not been reported. To determine the fluorescent reporter best suited for work in R. palustris, the fluorescence of wild type R. palustris was determined (Materials and Methods) for the excitation and emission wavelengths of GFPuv, enhanced yellow fluorescent protein (eYFP), and monomeric red fluorescent protein (mRFP) (Figure 1c).…”
Section: Fluorescent Reporters For Parts Characterizationmentioning
confidence: 99%